Are in vitro cytotoxicity assessments of environmental samples useful for characterizing the risk of exposure to multiple contaminants at the workplace? A systematic review - Viegas, Carla (2022)
Project “Occupational exposure of ambulance drivers to bioburden” (IPL/2020/BIO-AmbuDrivers_ESTeSL).